التحكم في أنظمة الطائرات بدون طيار باستخدام الخوارزميات الهجينة بين PID وAI - جمال عبد الرحمن الطيف الصغير (Surman Journal of Science and Technology, 2025)
This scientific paper aims to study the design and evaluation of an intelligent control system for Unmanned Aerial Vehicles (UAVs) based on the integration of the traditional PID (Proportional–Integral–Derivative) controller and Artificial Intelligence (AI) techniques such as Neural Networks (NN) and Genetic Algorithms (GA). The significance of this research lies in improving the performance and stability of flight systems under complex and constantly changing operating conditions, where hybrid algorithms demonstrate a superior ability to handle disturbances and noise compared to traditional systems. A simulation model was developed using MATLAB/Simulink to test the performance of the proposed system. The results showed a remarkable improvement in performance indicators such as settling time, error reduction, and trajectory tracking capability. The study recommends adopting this methodology in future operational systems for UAVs, especially in sensitive environments like security surveillance and smart delivery.